Pengaruh kualitas pelayanan, persepsi harga, dan lokasi terhadap keputusan menginap di hotel POP Kelapa Gading - Hastoko, Yosafat Puji; Stevany, Stevany (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of service quality, price perception, and location on purchasing decisions. The population in this study are customers who stay at Pop Hotel Kelapa Gading. The sampling technique used accidental sampling as many as 100 respondents. The data collection method used a questionnaire distributed to respondents and this analysis used multiple linear regression. The results showed that the service quality variable had an effect of 34.1% on purchasing decisions, the price perception variable had an effect of 49.8% on purchasing decisions, the location variable had an effect of 47.8% on purchasing decisions and from the results of this analysis it can be concluded that the quality service, perception of price and location affect purchasing decisions at Pop! Hotel Kelapa Gading either partially or simultaneously. This means that the independent variables consisting of service quality, price perception, and location simultaneously are 61.1% of purchasing decisions. While the remaining 38.9% is a variable others not listed in the research model.